Case Report: Kounis syndrome due to cryptopteran bite - Liao, Rui; Cheng, Shengjie; Xu, Nan (Frontiers in Cardiovascular Medicine, 2024)
Background Kounis syndrome is an acute coronary syndrome (ACS) caused by allergic reactions, including coronary artery spasm (type I) caused by allergies without coronary predisposing factors, pre-existing coronary atherosclerosis, and coronary artery disease. Anaphylaxis leads to plaque rupture or erosion leading to acute myocardial infarction (type II) and acute coronary stent thrombosis (type III). Here we share a case of Kounis syndrome type I caused by an allergy caused by a Cryptopteran bite. Case presentation A 47-year-old woman was admitted to the hospital due to an insect bite for 2 days and chest distress for more than 3 h. Outside the hospital, electrocardiogram(ECG) showed sinus rhythm, ST-segment elevation in leads V1–V3, high-sensitivity troponin 2.54 ng/ml(0–0.5 ng/ml). One hour later, the ECG of the patient showed that the ST segment elevation of lead V1–V4 was 0.10–0.20 mV. Emergency coronary angiography showed coronary spasm and moderate lumen stenosis in the middle segment of left anterior descending artery (LAD). After treatment, the patient's symptoms were relieved, and the ST segment of lead V1–V4 of electrocardiogram returned to normal. Conclusion Kunis syndrome is a life-threatening condition that can also cause myocardial ischemic injury in patients with or without coronary artery disease. Timely identification and anti-allergic treatment can achieve a good prognosis.